Gaya Penulisan Media Musik: - Arie Afrizal; Septiawan Santana Kurnia (UNISBA Press, 2023)
Abstrack. The path of development of music journalism is increasingly varied, with some mainstream media still promoting market music and some alternative media still consistently presenting music outside the industrial market. In a music media there are a lot of writings in it, such as news articles, articles, features and reviews. Several review writings began to mushroom in various music media, whether it's a review of a band, single or album. Therefore, music media journalists need an in-depth understanding and observation of the review articles they will write. As in its definition, music journalism is the activity of criticizing and reporting media on music topics. In music writing, of course, it is closely related to criticism, the criticism needed in music writing is sharp and intelligent criticism of a work. The purpose of music criticism is the consideration of good and bad about the ability of a person or group to produce music or musical works in musical performances. Music journalism is clearly writing about music, but the two main types of writing styles that tend to be published are interviews that gravitate towards feature writings from bands, individuals or people connected with music or reviews of major events, such as gigs, physical releases, books, and broadcast online (Mark Leverton: 2010). Music journalism also has a fairly narrow meaning, namely reporting or reporting within the scope of music but still relying on the principles of journalism itself, namely based on facts, or events that occur objectively, not fiction. One of the products of a music journalism product is review writing. Review writing itself is a concluding article, a review of several observed objects, such as writings, books, journals, gadgets, applications, food, electronics, films, music and others. With a review article, the reader will know the advantages, disadvantages and quality of a work or product. Review writing has the main purpose of providing information to the reader in order to know a summary of an object. A review also has a general structure that begins with an introduction and ends with an evaluation. This research focuses on the application of journalistic rules in review writing in the music media Rich Music Online. This study uses a qualitative method with a case study approach. In this case, the researcher is trying to find out the application of journalistic rules to review writing in the music media Rich Music Online. Abstrak. Alur perkembangan jurnalisme musik makin sini makin bervariasi, dengan beberapa media mainstream masih mengedepankan musik-musik pasar dan ada pula beberapa media alternatif yang masih konsisten menyuguhkan musik-musik di luar pasar industri. Dalam sebuah media musik banyak sekali tulisan-tulisan yang ada di dalamnya, seperti tulisan berita, artikel, feature dan review. Beberapa tulisan review pun mulai menjamur di berbagai media musik, mau itu review band, single ataupun album. Oleh karena itulah para jurnalis media musik membutuhkan pemahaman dan observasi mendalam mengenai tulisan review yang akan ditulisnya. Seperti pada pengertiannya jurnalisme musik merupakan kegiatan mengkritik dan pelaporan media mengenai topik musik. Dalam penulisan musik tentunya lekat dengan kritik, kritik yang dibutuhkan dalam penulisan musik yaitu kritik tajam dan cerdas terhadap suatu hasil karya. Maksud dari kritik musik adalah pertimbangan baik dan buruk terhadap kemampuan seseorang atau kelompok dalam memproduksi musik atau karya musik dalam pertunjukan musik. Jurnalisme musik jelas menulis tentang musik, tetapi dua jenis gaya penulisan utama yang cenderung dipublikasikan adalah wawancara yang condong ke tulisan feature dari band, individu atau orang yang terhubung dengan urusan musik atau ulasan dari peristiwa-peristiwa besar, seperti gigs, rilisan fisik, buku, dan siarain online (Mark leverton: 2010). Jurnalisme musik juga memiliki artian yang cukup mengkerucut, yaitu pelaporan atau reportase dalam lingkup musik namun tetap bersandar pada kaidah jurnalisme itu sendiri, yaitu berdasarkan fakta, atau peristiwa yang terjadi secara objektif, bukan fiksi. Salah satu produk dari sebuah produk jurnalisme musik adalah tulisan review. Tulisan review sendiri merupakan sebuah tulisan simpulan, tinjauan dari beberapa objek yang diamati, seperti tulisan, buku, jurnal, gadget, aplikasi, makanan, elektronik, film, musik dan lainnya. Dengan adanya sebuah tulisan review pembaca akan mengetahui kelebihan, kekurangan dan kualitas dari suatu karya atau produk. Tulisan review mempunyai tujuan utama yaitu untuk memberikan informasi kepada pembaca agar mengetahui ringkasan dari sebuah objek. Sebuah review pun memiliki sebuah struktur yang umum yaitu diawali dengan pengenalan dan diakhiri dengan sebuah evaluasi. Penelitian ini berfokus pada penerapan kaidah-kaidah jurnalistik pada tulisan review dalam media musik Rich Music Online. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus. Dalam hal ini peneliti berusaha mencari tahu penerapan kaidah-kaidah jurnalistik pada tulisan review dalam media musik Rich Music Online.